2012
DOI: 10.5581/1516-8484.20120048
|View full text |Cite
|
Sign up to set email alerts
|

Dengue antibodies in blood donors

Abstract: BackgroundDengue is an urban arbovirus whose etiologic agent is a virus of the genus Flavorius with four distinct antigen serotypes (DENV-1, DENV-2, DENV-3 and DENV-4) that is transmitted to humans through the bite of the mosquito Aedes aegypti. The Campo Mourão region in Brazil is endemic for dengue fever.ObtectiveThe aim of this study was to evaluate the presence of IgG and IgM antibodies specific to the four serotypes of dengue in donors of the blood donor service in the city of Campo Mourão.MethodsEpidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Data of this study showed predominance of male donors (98.3%) over female donors (1.70%) with the majority of donors (76.18%) of <35 years age group. These findings are similar to findings of Ribas-Silva and Andressa[ 7 ] who reported 63.8% of male donors with 30% of donors within 30-39 years age group.…”
Section: Discussionsupporting
confidence: 92%
“…Data of this study showed predominance of male donors (98.3%) over female donors (1.70%) with the majority of donors (76.18%) of <35 years age group. These findings are similar to findings of Ribas-Silva and Andressa[ 7 ] who reported 63.8% of male donors with 30% of donors within 30-39 years age group.…”
Section: Discussionsupporting
confidence: 92%
“…The reason for this low IgG‐positive rate may be: (1) the number of blood donors with dengue infection in this area was previously lower; (2) it maybe caused by the recent DENV outbreak in the neighbouring area, and the virus had just started to spread in Liuzhou during that time; and (3) the sample size may be not large enough. Although these rates are much lower than those reported in donors in the Guangdong Province during the severe dengue outbreak in 2014 and other Southeast Asian countries (Harif et al ., ; Low et al ., ), the geographical features of Guangxi and its closeness to the surrounding dengue seasonal endemic regions may make it vulnerable to future outbreaks (Dias et al ., ; Ribas‐Silva & Eid, ).…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Viraemic donor rate may be as high as 0.4% during outbreaks, 21 with a risk of transfusion-transmitted DENV (TT-DENV) calculated as 1 in 1300 donations in Puerto Rico. 22 Questions on the potential transmission of DENV by transfusion increased after the documentation of the risk of transmission of the West Nile virus (WNV) by Biggerstaff & Petersen 23 and Biggerstaff & Petersen. 24 It seems highly probable that DENV is transmitted in a manner similar to the WNV as both are arboviruses within the same family of Flaviviridae.…”
Section: This Recent Rapid Expansion Throughout the World And In Burkinamentioning
confidence: 99%
“…The asymptomatic and subclinical cases, estimated at around 50‐85% of DENV infections, constitute the main concern regarding transfusion safety as symptomatic cases are assumed to be rejected at the pre‐donation screening Previous studies reported the presence of DENV in blood donors in Honduras, Brazil, Australia, Puerto Rico and Saudi Arabia . Viraemic donor rate may be as high as 0.4% during outbreaks, with a risk of transfusion‐transmitted DENV (TT‐DENV) calculated as 1 in 1300 donations in Puerto Rico …”
mentioning
confidence: 99%